Exploring the phytochemical profile, antioxidant and anti-inflammatory potential of Bidens pilosa: A Systematic Review - Ekom Monday Etukudo; Ibe Michael Usman; Augustine Oviosun; Vivian Onyinye Ojiakor; Isxaq Abdi Jama; Wusa Makena; Danladi Makeri; Elna Owembabazi; Patrick Maduabuchi Aja; Josiah Ifie; Ilemobayo Victor Fasogbon; Victor Bassey Archibong; et al. (Frontiers in Pharmacology)
Medicinal plants have garnered significant attention for their potential in treating various human diseases. Many of these plants exhibit antioxidant and anti-inflammatory properties, which are crucial for mitigating the impact of oxidative stress and inflammation implicated in numerous clinical conditions. This review investigated the antioxidant and anti-inflammatory properties of medicinal plants, particularly Bidens pilosa, and their potential applications in disease management. A structured systematic approach was employed for this analysis. Scopus, PubMed, and Web of Science were searched using the following search algorithm: (“Bidens pilosa”) AND (“antioxidant”) AND (“anti-inflammatory” OR “anti-inflammatory”) on the second of April 2025 without any filters. At the end of the title, abstract and full text screening, only 50 articles met the inclusion criteria and hence included in the study. Most (35/50, 70%) were published within the years 2014–2024. Of the 50 studies, 23 (46%) were done in Africa, 14 (28%) in Asia, and 11 (22%) in South America. Most studies were done in a laboratory dish (29/50, 58%), with a smaller number done in animals (12/50, 24%). Fourteen percent (14%) of the studies used both in vivo and in vitro methods, and 4% were carried out on people. Out of the 50 studies, leaves were looked at most often (23 or 46%), followed by the whole plant (19 or 38%). Bidens pilosa lowered the tissue levels of tumor necrosis factor (TNF) and interleukin (IL)-6, IL-1β, and IL-8. It also improved the tissue levels of antioxidants glutathione while reducing lipid peroxidation via malondialdehyde (MDA). In conclusion, all the studies examined in the present study reported that Bidens pilosa possess antioxidant and anti-inflammatory potential, hence holding great promise in the management of oxidative stress and inflammation-related conditions.